Meteorological measurement systems - Brock, Fred V.; Richardson, Scott J. (Oxford Univ. Press, 2001)
1. Overview. 2. Barometry. 3. Static Performance Characteristics. 4. Thermometry. 5. Hygrometry. 6. Dynamic Performance Characteristics, Part 1. 7. Anemometry. 8. Dynamic Performance Characteristics, Part 2. 9. Precipitation Rate. 10. Solar and Earth Radiation. 11. Visibility and Cloud Height. 12. Upper Air Measurements. 13. Sampling and Analog-to-Digital Conversion. A. Units and Constants. B. Thermistor Circuit Analysis. C.A Data Logger. D. Circuits. E. Geophysical Coordinate System. F. Instrumentation Glossary. Index.